Surface modification of commercial anion exchange membrane for the inactivation of Escherichia coli - Mudau, Fulufhelo H.; Muvhiiwa, Ralph F.; Motsa, Machawe M.; De Kock, Lueta-Ann; Hassard, Francis (Springer, 2026)
Modifying membranes with antimicrobial nanoparticles enhances antifouling properties and enables rapid disinfection during water treatment. Here, silver (Ag) and copper (Cu) particles were formed on a commercial anionic exchange membranes using a two-step ion-mediated surface-reduction process consisting of a 24-h sodium borohydride treatment followed by a 24-h reaction with Ag and Cu precursor solutions (0.01–0.1 M). Scanning electron microscopy with energy-dispersive spectrometry confirmed uniform Ag and Cu particle distribution on the membrane surface. Increasing precursor concentration enlarged the Ag particle diameters from 167.7 ± 2.2 nm to 652.2 ± 23.4 nm and Cu from 117.8 ± 3.4 nm to 606.5 ± 16.6 nm, with metal content of 0.05 ± 0.001–0.17 ± 0.01 mg·cm2 (Ag) and 1.05 ± 0.01–2.13 ± 0.03 mg·cm2 (Cu). Metal leaching after 14 days was low (Ag: 3.11 ± 0.24–6.62 ± 0.12 ppb; Cu: 2.75 ± 0.1–5.32 ± 0.1 ppb), within World Health Organization drinking water limits. The modified membranes achieved up to 8-log inactivation of Escherichia coli within 1–4 h. The most effective Ag and Cu membranes (lowest metal loading) exhibited specific inactivation rates of 13.68 ± 0.93 (mg·cm2)⁻1 for Ag and 1.69 ± 0.14 (mg·cm2)⁻1 for Cu in 2 h. Ag exhibited the highest antimicrobial efficiency per unit metal, while high-loading Cu disinfects fastest, together showing metal-modified anionic membranes provide stable, low-leaching antimicrobial performance suitable emergency treatment.
Keywords: 4004 Chemical Engineering; 40 Engineering; 34 Chemical Sciences; Environmental Sciences